No evidence for future planning in Canada jays (Perisoreus canadensis). (8th December 2021) - Martin, R. Jeffrey; Martin, Glynis K.; Roberts, William A.; Sherry, David F.
Abstract : In the past 20 years, research in animal cognition has challenged the belief that complex cognitive processes are uniquely human. At the forefront of these challenges has been research on mental time travel and future planning in jays. We tested whether Canada jays ( Perisoreus canadensis ) demonstrated future planning, using a procedure that has produced evidence of future planning in California scrub-jays. Future planning in this procedure is caching in locations where the bird will predictably experience a lack of food in the future. Canada jays showed no evidence of future planning in this sense and instead cached in the location where food was usually available, opposite to the behaviour described for California scrub-jays. We provide potential explanations for these differing results adding to the recent debates about the role of complex cognition in corvid caching strategies.